Status and trends of graduate library and information science researches submitted to library schools in Metro Manila, 1992-2007 - Dery, Zipporah M. (2010)
Research performs a vital role in the development of library and information science (LIS) because it informs the theory and practice of the field through a systematic method of inquiry. Analysis of the content of LIS researches could reveal the state and direction of research initiatives as well as the needs and potentials of LIS research towards the development of the LIS theory and practice. It is in this light that this study delved on the status and trends of graduate LIS researches submitted to library schools in Metro Manila from 1992 to 2007.